Shear Deformation and the Buckling of Columns, Revisited - James M. Kelly (Theory and Applications of Engineering Research Vol. 1, 2023)
The question of the correct approach to analyze the buckling of columns in which shear deformation is important continues to be a matter of some uncertainty. There are few textbooks that treat this problem definitively. Most describe one solution or another, with the statement that they do not differ very much in practice. However there are situations where different theories can result in very different predictions; this paper explains why. It will be shown that the prediction of buckling loads for columns that are very weak in shear is crucially dependent on the choice of the direction for the axial load of the column in the buckled configuration. Examples of three separate selections for the axial load direction will be shown to lead to very different predictions of the buckling load. The results can differ by orders of magnitude. Note: these predictions are all valid but the type of columns must be taken into consideration.